2016
DOI: 10.7603/s40681-016-0020-6
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium deficiency and oxidative stress: an update

Abstract: Magnesium deficiency (MgD) has been shown to impact numerous biological processes at the cellular and molecular levels. In the present review, we discuss the relationship between MgD and oxidative stress (OS). MgD is accompanied by increased levels of OS markers such as lipid, protein and DNA oxidative modification products. Additionally, a relationship was detected between MgD and a weakened antioxidant defence. Different mechanisms associated with MgD are involved in the development and maintenance of OS. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
102
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(118 citation statements)
references
References 76 publications
3
102
0
2
Order By: Relevance
“…Owing to the positive impact of citrate containing fluids on the hemodynamic parameters and redox status of HD patients, it has recently been proposed to use citrate, instead of the less physiologic acetate, in DFs to improve the outcome of HD process in clinical practice [16,35]. Moreover, Mg deficiency is involved in the development and maintenance of an elevated oxidative stress status, contributing to CVD in HD patients [11,24,36]. Therefore, the use of DFs with high Mg concentrations could prevent uremia-induced oxidative stress in HD patients [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Owing to the positive impact of citrate containing fluids on the hemodynamic parameters and redox status of HD patients, it has recently been proposed to use citrate, instead of the less physiologic acetate, in DFs to improve the outcome of HD process in clinical practice [16,35]. Moreover, Mg deficiency is involved in the development and maintenance of an elevated oxidative stress status, contributing to CVD in HD patients [11,24,36]. Therefore, the use of DFs with high Mg concentrations could prevent uremia-induced oxidative stress in HD patients [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Serum Mg in HD patients is affected by the dialysate Mg concentration, which is low (0.5 mM) as standard [23,28,46], and may induce a post-dialytic hypomagnesemia and undesirable hemodynamic effects, such as hypotension, arrhythmia, and calcification) [23,30,46,47]. Furthermore, due to antiinflammatory and antioxidant properties of Mg, hypomagnesemia has also been associated with increased oxidative-inflammatory stress [36,48]. In fact, low Mg transitorily leads to pro-oxidant effects, exacerbating ROS production [36,49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another meta-analysis, Mg supplementation was shown to reduce fasting plasma glucose in diabetics and improve HOMA-IR and plasma glucose (in a 2 h oral glucose tolerance test) in persons at high risk of diabetes [50]. The mechanisms by which Mg deficiency may increase diabetes risk are poorly understood but may involve increased oxidative stress and inflammation [35,51,52]. It is important to mention that this study does not provide any information on the temporality of the reported associations with serum Mg given the cross-sectional design.…”
Section: Discussionmentioning
confidence: 99%